Child-friendly village: Promoting growth without devices in the digital age - Sri Muniroch; Siti Masitoh; Rina Sari; Aulia Mar'atussholehah (University of Merdeka Malang, 2025)
Brubuh Hamlet in Kalipang Village, Sutojayan District, Blitar Regency holds strong potential to become a child-friendly area, particularly in supporting children’s growth and development without reliance on digital devices. In response to this, a community service program on Child-Friendly Village Development was carried out with two main objectives: (a) to identify and explore the assets and potentials of the community to create a supportive, child-friendly environment; and (b) to encourage community members to take action toward realizing this vision. Using the Asset-Based Community Development (ABCD) approach, various local assets were mapped—including individual skills, physical infrastructure, social capital, natural resources, cultural values, and religious traditions. Building on this foundation, actions were implemented through educational workshops on the importance of a gadget-free developmental environment for children, as well as the construction of a play area equipped with facilities designed to stimulate children’s physical, cognitive, and emotional development. As a result of this initiative, residents became inspired to propose and initiate further community-driven activities, demonstrating increased ownership and engagement in building a child-friendly environment.